Louisiana and the Coronavirus Pandemic: A Case Study and Future Scenarios - Deggins, Vanessa (My University, 2024)
In the lead up to the 2020 coronavirus pandemic, United States residents were grappling with widespread increase in cost of living, mainly in the form of housing and cost of food. Specific to Louisiana, it had the same issues, as well as a host of widespread chronic health issues, a lack of living wage and large-scale effects of climate change with little will to make needed policy changes. This thesis evaluates media coverage during the first three months of the 2020 coronavirus pandemic to evaluate how media coverage about the pandemic was framed in relation to social issues specific to the state of Louisiana and how this could affect its future. A media and literature review were conducted and used to craft two future scenarios. The literature review was helped to develop a list of social issues affecting Louisiana just before the beginning of the pandemic in the United States, which is when the first U.S. case was reported. The literature review revealed that social issues in Louisiana and its causes and policies have been studied in-depth in academic circles. It provided a comprehensive list of the issues, how they are connected and the root causes. The media in its state in 2020, provided mostly shorter-format reporting that relied heavily on statistics but not much context or historical perspective. It did provide many quotes from state politicians to develop an understanding of their ideologies and the political landscape of the state of Louisiana.
Keywords: coronavirus, Sars-Cov-2, Louisiana, social issues, chronic health issues, living wage, climate change, food security